ANALYSIS OF TECHNICAL CONSIDERATIONS FOR KARYA MAJU VILLAGE TOURISM DESTINATIONS, BARITO KUALA REGENCY - Supar, Evan Elianto; Razak, Humairoh; Aina, Noor (Border: Jurnal Arsitektur, 2022)
The designation of Karya Maju Village as part of the Talaran Setara Tourism Area by the Regent of Barito Kuala, is a strategic step to provide improvement for the people in the area. Through developing plantation potential and opportunities, tourist destinations, especially those in Karya Maju Village, are trying to elevate agrotourism attractions as superior. In an effort to create a sustainable tourism area, other aspects need to be taken into consideration, including attractions, supporting facilities, achievements and additional facilities. This research uses a qualitative approach through comparative descriptions of ideal technical aspects with the real conditions encountered. Through this analysis of technical considerations, it is hoped that we can provide recommendations for the physical components of the area as a whole.